2000
DOI: 10.1007/s004240000426
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate stimulates insulin secretion by shifting the gating of L-type Ca2+ currents in mouse pancreatic B-cells towards negative potentials

Abstract: The effects of the chaotrophic anion perchlorate (ClO4-) on glucose-induced electrical activity, exocytosis and ion channel activity in mouse pancreatic B-cells were investigated by patch-clamp recordings and capacitance measurements. ClO4- stimulated glucose-induced electrical activity and increased the action potential frequency by 70% whilst not affecting the membrane potential when applied in the presence of a subthreshold concentration of the sugar. ClO4- did not influence ATP-dependent K (KATP) channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2002
2002
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 29 publications
6
25
0
1
Order By: Relevance
“…The idea that this effect is due to the peptide interfering with the voltage-gated Ca2+ channels is consistent with the fact that PACAP-27 overall increases depolarization-elicited Ca2+ influx by @35% (Figs. 2, 4,6), in a fashion reminiscent of the action of the chaotrophic anion perchlorate [28]. Taken together, these actions account for 1.41.35=1.9 or 90% stimulation, close to the increase in insulin release observed when experimenting at 10 mM and 20 mM glucose (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The idea that this effect is due to the peptide interfering with the voltage-gated Ca2+ channels is consistent with the fact that PACAP-27 overall increases depolarization-elicited Ca2+ influx by @35% (Figs. 2, 4,6), in a fashion reminiscent of the action of the chaotrophic anion perchlorate [28]. Taken together, these actions account for 1.41.35=1.9 or 90% stimulation, close to the increase in insulin release observed when experimenting at 10 mM and 20 mM glucose (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The action potentials in the INS-1 cells are Ca2+ dependent and the observed effect can thus be extrapolated to correspond to an enhanced Ca2+ influx which in turn associates with the acceleration of insulin release. This PACAP-induced acceleration of electrical activity is reminiscent of the effects of the chaotrophic anion perchlorate [28]. When increasing the extracellular glucose concentration, the generated pattern of electrical activity was so irregular that a straightforward analysis of the glucose-dependent action of PACAP-27 was not possible (not shown).…”
Section: Ca2+ Currents and Exocytosis At Different Glucose Concentratmentioning
confidence: 95%
“…This pharmacological phenotype was achieved without detectable alterations in channel gating or Ca v 1.2 α1 expression. High-affinity DHP binding in brain was reduced to a level (20%) known to be associated with Ca v 1.3 (1,30 (15,33), such drugs theoretically allow stimulation of insulin secretion in a glucose-sensitive manner (33). Our data clearly revealed that Ca v 1.3 LTCCs are not suitable targets for insulin secretagogues because we found no evidence for the acute regulation of β cell Ca 2+ currents or insulin secretion by DHPs in Ca v 1.2DHP -/-mice.…”
Section: Discussionmentioning
confidence: 99%
“…One poorly understood mechanism involves the effects of anions on I Ca . Replacing Cl − with various substituting anions influences many Ca 2+ -mediated processes including contractility of cardiac and skeletal muscle, hormone secretion, and neurotransmitter release [8][16]. An important contributor to these anion effects is the modulation of L-type Ca 2+ currents (I Ca ) [8][10], [17], [18].…”
Section: Introductionmentioning
confidence: 99%